A dynamic routing scheme for underwater acoustic sensor networks in submarine disaster applications - Jiang, Peng; Wang, Hao; Xiong, Zhiwen (Frontiers in Marine Science, 2024)
Introduction The ocean economy serves as a critical engine for the development of human society and economy, and its stable growth is of utmost importance. However, the frequent and unexpected occurrence of natural disasters, such as submarine disasters, poses significant threats to human society, especially disasters related to wave phenomena like the Ekman current, which has particularly prominent impacts. Methods The study proposes a dynamic routing scheme for underwater acoustic sensor networks. It establishes a cone-shaped distributed network, utilizing autonomous underwater vehicles to collect crucial data from nodes deployed on the seabed and transmitting it through the underwater cone-shaped distributed sensor network. Additionally, it adopts source location protection (SLP) technology to ensure the privacy of source locations. To validate the practicality and stability of this scheme, simulation experiments targeting the Ekman current were conducted in MATLAB. Results The experimental results demonstrate that the cone–SLP network significantly reduces the frequency of routing information exchange and energy consumption among acoustic sensors, effectively enhancing the economy and durability of the sensor network. Furthermore, it exhibits robust practicality and high stability in complex and variable submarine environments. Discussion This research not only provides a practical method for effectively monitoring submarine disasters but also offers valuable experience and significant reference value for other similar projects, playing a more crucial role in the sustainable development of the ocean economy.